Efecto de los compuestos vitaminicos en el desarrollo de la langosta azul cherax quadricarinatus a nivel de laboratorio - Zapata Porras, Katherine Santos (2007)
The present investigation one carries out in the Laboratory of Maricultura of the School of Acuacultura, of the Ability of Agricultural Sciences of the University of Machala. The objective outlined for the investigation is: 1. To determine the effect of the compound vitamínicos in the development of the lobster (Cherax quadricarinatus) and to establish the appropriate dose of the vitamin for their growth. For the experimental work 3 treatments settled down; 2 grams, 2,5 grams and 3 grams of Vitamin. The averages of the treatment of 3 grams went superiors statistically to the other treatments. You doesn't detect significant statistical difference due to the longitude. You concludes in that: the treatment of 3 grams was significantly respectively better than the other treatment 2 and 2,5 grams, the weight was statistically better than the longitude in the treatment of 3 grams of vitamins, the parameters abióticos (Temperature, pH and Oxygen disuelt) they were a little abnormal.